Preparation and characterization of Posaconazole as a Nano-micelles using d-α-Tocopheryl polyethylene glycol 1000 succinate (TPGS) - abdulqader, Alaa abdul elah; sultan, Nawal A. Rajab (Iraqi Journal of Pharmaceutical Sciences, 2023)
It is important to note that Posaconazole (POCZ) is a newly developed extended-spectrum triazole that belongs to BCS class II and has a solubility of less than 1µg/ml. In patients with a weakened immune system, POCZ has been shown to be effective as an antifungal treatment for invasive infections caused by candida and aspergillus species. The nano-micelles technique can be used to increase POCZ solubility. In order to increase their apparent solubility in water, nano-micelles are made by combining macromolecules that self-assemble into ordered structures capable of entrapping hydrophobic drug molecules in the interior domain. Dispersed colloidal systems, of which nano-micelles are a subset, are a large and diverse group. Composed of a phase that is itself dispersed throughout a medium (continuous phase). Surfactants form a colloidal solution when their concentration in solution is higher than their critical micelle concentration (CMC). POCZ nano-micelles are made with TPGS and tween 80. In this study, we prepared six different formulations and analyzed their particle size, polydispersity index (PDI), entrapment efficiency (EE), drug loadings (DL), saturation solubility, and in-vitro release. The drug-loaded nano-micelles of the Posaconazole formula (POCZ6) were characterized, and their properties were found to be: Particle size (90.68 nm), PDI (0.27), EE (94%), DL (10.3%), and best solubility factor (1133) are all better in the TPGS: tween80(1:5:3) ratio than in the pure drug. An in-vitro release study was conducted, and the results showed that the chosen formula POCZ6 released the entire dose of drug in 70 minutes, compared to only 23% for pure drug. Fourier transform infrared microscopy and other forms of investigation (FTIR). As can be seen from the data, there are no interactions or changes in the major peaks of Posaconazole when it is combined with polymer and surfactant.